Covert Communication in MIMO-OFDM System Using Pseudo Random Location of Fake Subcarriers - Hudhajanto, Rizky Pratama; Astawa, I Gede Puja; Sudarsono, Amang (EMITTER International Journal of Engineering Technology, 2016)
Multiple-Input Multiple-Output Orthogonal Frequency Division Multiplexing (MIMO-OFDM) is the most used wireless transmission scheme in the world. However, its security is the interesting problem to discuss if we want to use this scheme to transmit a sensitive data, such as in the military and commercial communication systems. In this paper, we propose a new method to increase the security of MIMO-OFDM system using the change of location of fake subcarrier. The fake subcarriersâ location is generated per packet of data using Pseudo Random sequence generator. The simulation results show that the proposed scheme does not decrease the performance of conventional MIMO-OFDM. The attacker or eavesdropper gets worse Bit Error Rate (BER) than the legal receiver compared to the conventional MIMO-OFDM system.